Implementasi Absensi Berbasis Digital untuk Meningkatkan Disiplin Siswa di SMPN 1 Praya Kabupaten Lombok Tengah - Arnita Rosniayanti; Lalu Andri Rafani; Mohamad Mustari (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The development of Information and Communication Technology (ICT) has encouraged schools to improve their administrative systems, including student attendance management. This study aims to describe the implementation of a digital attendance system in enhancing student discipline at SMPN 1 Praya, Central Lombok Regency. The research employed a qualitative method with a descriptive approach. Data were collected through observations, interviews, and documentation involving the principal, teachers, and students as research informants. The findings reveal that the barcode-based digital attendance system effectively improves student discipline, particularly in terms of punctuality, compliance with school regulations, and responsibility for participating in learning activities until completion. The system is implemented through arrival attendance before 07:15 AM (WITA) and departure attendance at 01:15 PM (WITA). Furthermore, the use of manual attendance as an additional verification mechanism enhances the accuracy and accountability of attendance records. Although several challenges remain, including network disruptions, system errors, and attempts at student misconduct, the school addresses these issues through direct supervision, disciplinary sanctions, and periodic evaluations. Therefore, the digital attendance system can be considered an effective innovation for improving student discipline and enhancing school attendance administration.